The impact of coffee consumption on health quality among adolescent girls (Nursing and Health Sciences Journal (NHSJ), 2025)
Coffee is one of the most consumed beverages among adolescents, including adolescent girls, often for reasons such as improving concentration, reducing sleepiness, or as part of lifestyle habits. However, excessive coffee consumption may have adverse effects on both physical and psychological health. This study aimed to investigate the impact of coffee consumption on the health quality of adolescent girls. The research employed an analytical quantitative design with a cross-sectional approach. The study population consisted of 117 female high school students in Bekasi, with samples selected using purposive sampling. Data were collected through questionnaires on coffee consumption patterns and health status, including sleep quality, anxiety levels, learning concentration, and physical complaints. Data were analyzed using the chi-square test to determine the relationship between coffee consumption and health quality. The findings showed that most respondents consumed coffee 1-2 times per day, either in the morning or at night. Excessive coffee consumption was significantly associated with poor sleep quality (p = 0.046), increased anxiety levels (p = 0.009), decreased concentration (p < 0.0001), and anemia (p < 0.0001). Coffee consumption negatively affects the health quality of adolescent girls, particularly in aspects related to sleep, psychological well-being, and concentration. Education on balanced and healthy coffee consumption should be provided to adolescents early on to prevent long-term negative health impacts.